The Epigenetic Modulation of Cancer and Immune Pathways in Hepatitis B Virus-Associated Hepatocellular Carcinoma: The Influence of HBx and miRNA Dysregulation - Sartorius, Kurt; An, Ping; Winkler, Cheryl; Chuturgoon, Anil; Li, Xiaodong; Makarova, Julia; Kramvis, Anna (Frontiers in Immunology, 2021)
Hepatitis B virus (HBV)-associated hepatocellular carcinoma (HBV-HCC) pathogenesis is fuelled by persistent HBV infection that stealthily maintains a delicate balance between viral replication and evasion of the host immune system. HBV is remarkably adept at using a combination of both its own, as well as host machinery to ensure its own replication and survival. A key tool in its arsenal, is the HBx protein which can manipulate the epigenetic landscape to decrease its own viral load and enhance persistence, as well as manage host genome epigenetic responses to the presence of viral infection. The HBx protein can initiate epigenetic modifications to dysregulate miRNA expression which, in turn, can regulate downstream epigenetic changes in HBV-HCC pathogenesis. We attempt to link the HBx and miRNA induced epigenetic modulations that influence both the HBV and host genome expression in HBV-HCC pathogenesis. In particular, the review investigates the interplay between CHB infection, the silencing role of miRNA, epigenetic change, immune system expression and HBV-HCC pathogenesis. The review demonstrates exactly how HBx-dysregulated miRNA in HBV-HCC pathogenesis influence and are influenced by epigenetic changes to modulate both viral and host genome expression. In particular, the review identifies a specific subset of HBx induced epigenetic miRNA pathways in HBV-HCC pathogenesis demonstrating the complex interplay between HBV infection, epigenetic change, disease and immune response. The wide-ranging influence of epigenetic change and miRNA modulation offers considerable potential as a therapeutic option in HBV-HCC.